Water security and ecosystem-based adaptation in the headwaters of Cantareira Water Supply System, Brazil - Taffarello, Denise (2016)
Water quantity, availability and, particularly, quality of Brazilian freshwater is under progessive degradation due to Anthropocene\'s environmental changing conditions. Strategies of Ecosystem-based Adaptation (EbA) are essential to mitigate these impacts. This Ph.D. thesis proposes a new model of water resources management, thereby integrating selfpurification and ecohydrologic processes to evaluate ecosystem services from watershed under change. In Chapter 2, this thesis examinates the payment for hydrologic cosystem services (Water-PES) in Brazilian Atlantic Forest and points ecohydrologic variables useful for assessing and further valuing hydrologic services. In Chapter 3, this thesis discusses proposals for freshwater monitoring plan which integrate quali-quantitative aspects for EbA and Water-PES projects. Therefore, in Chapter 4 experimental quali-quantative freshwater data from in-situ field observations are investigated according land-use/land-cover (LULC) in headwaters of water supply systems. In Chapter 5, through simulated impacts on freshwater yield from scenarios of LULC change, the grey water footprint (greyWF) is assessed, as well as environmental sustainability of sub-basins is depicted from a new ecohydrologic index for assessing hydrologic services. The methodology is performed using through field sampling and lab-analysing of physico-chemical, biologic and hydraulic variables in nested sub-basins draining to the Cantareira Water Supply System, in Sao Paulo and Minas Gerais states, Brazil. These areas participate in the Water-PES projects Water Producer/PCJ and Water Conservator at headwaters of Piracicaba watershed, during recent severe drought conditions between years 2013-15. The greyWF is estimated from outputs of time series simulated through ecohydrologic model Soil and Water Assessment Tool (SWAT). Under assumption of continuity of Water-PES projects, and using the same series of hydrometorological records for a common period (2008-2014), freshwater quali-quantitative impacts are performed through three LULC scenarios: past situation \"S1\" (year 1990), current situation \"S2\" (year 2010) and future situation \"S2+EbA\" (year 2035). From these scenarios, flow and load duration curves, mean water yields, greyWF and seasonal variabilities, were simulated. Through this research, continuous-monitoring Data Collecting Stations were installed in public-private partnership encompassing EESC/USP, ANA, CPRM, CEMADEN, SMA, TNC, WWF and local mayors. This continuous monitoring is addressed to increase the system resilience, based on better decision-making for water security, in strategic headwaters not only for water supply, but also for environmental conservation. This doctoral thesis brings contributions to a better comprehension of anthropic impacts on water resources and for strategies of EbA in front of progressive rates of losses of ecosystem services. This PhD. thesis was part of three research initiatives which partly granted activities: (1) Thematic Project FAPESP 2008/58161-1 \"Assessment of Impacts and Vulnerability to Climate Change in Brazil and Strategies for Adaptation Options\"; (2) \"INCLINE - INterdisciplinary CLimate INvEstigation Center\" (NapMC/USP Núcleo de Apoio às Pesquisas em Mudanças Climáticas) and (3) \"Água Brasil\" Project, Banco do Brasil Foundation, WWF Brazil, ANA & FIPAI/EESC-USP.